Clinical outcomes and complications of reverse shoulder arthroplasty used for failed prior shoulder surgery: a systematic review and meta-analysis - Aaron J. Bois, MD, MSc, FRCSC; Paige Knight, MD; Khalifa Alhojailan, MD; Kamal I. Bohsali, MD (JSES International, 2020)
Background: Reverse shoulder arthroplasty (RSA) is frequently performed in the revision setting as a salvage procedure. The purpose of this study was to report the clinical outcomes and complication, reoperation, and revision rates after revision RSA (RRSA) stratified according to the primary shoulder procedure undergoing revision. Methods: Four databases (Embase, MEDLINE, SPORTDiscus, and Cochrane Controlled Trials Register) were searched for eligible studies published between January 1985 and September 2017. The primary outcomes of interest included pain, active range of motion, and functional outcome scores. Secondary outcomes included complication, reoperation, and revision rates. Results: A total of 43 studies (1041 shoulder arthroplasties) met the inclusion criteria, with a mean follow-up period of 43.8 months (range, 31.1-57.2 months). Pain scores improved in all groups; however, none reached statistical significance. Range of motion improved in all groups, except for external rotation in the RSA category. RRSA demonstrated significant improvements in the Simple Shoulder Test score and Constant score (CS) in the group undergoing hemiarthroplasty (HA) for fracture, CS in the group undergoing HA for other indications, and CS in the group undergoing anatomic total shoulder arthroplasty. Pooled complication rates were highest in the failed RSA group (56.2%), followed by the group undergoing HA for other indications (27.7%), total shoulder arthroplasty group (23.6%), soft-tissue repair group (20.6%), open reduction and internal fixation group (19.0%), and group undergoing HA for fracture (13.6%). Conclusions: Compared with other revision indications, RRSA for failed HA demonstrated the most favorable outcomes, whereas the highest complication and revision rates were observed in the RSA subgroup. This information is useful when establishing patient expectations regarding the risks, benefits, and complication and revision rates of RRSA.